2010
DOI: 10.1116/1.3474973
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, metastable phases, and demixing in a hafnia-titania nanolaminate annealed at high temperature

Abstract: Nanolaminate films with a nominal 5 nm HfO2–4 nm TiO2 bilayer architecture are sputter deposited on unheated fused silica and Au-coated glass substrates. Films on fused silica are postdeposition annealed from 573 to 1273 K and characterized by x-ray diffraction, scanning electron microscopy, Raman microscopy, and UV-visible-near IR spectrophotometry. The films show weak but progressive crystallization into orthorhombic (o) HfTiO4 when annealed up to 973 K. o-HfTiO4 is expected to form under bulk thermodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…1,3 The aforementioned double peak vicinal to the rutile standard, labeled A and B, as well as a lower angle peak, labeled C, were also observed after 24 h at 1273 K. Peak A is attributed to the (110) planes of TiO 2 :Hf as before, 1-3 but peak B is now attributed to hafnon (200) planes. 8 Peak C is attributed to hafnon (101) planes.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…1,3 The aforementioned double peak vicinal to the rutile standard, labeled A and B, as well as a lower angle peak, labeled C, were also observed after 24 h at 1273 K. Peak A is attributed to the (110) planes of TiO 2 :Hf as before, 1-3 but peak B is now attributed to hafnon (200) planes. 8 Peak C is attributed to hafnon (101) planes.…”
mentioning
confidence: 76%
“…[1][2][3] The as-grown film consists of nanocrystalline orthorhombic (o) HfTiO 4 . (o-HfTiO 4 is intrinsically unstable and demixes upon annealing above 973 K. 1,3 ). Post-deposition air annealing was carried out first at 1173 K for up to 192 h (denoted stage I).…”
mentioning
confidence: 99%
“…In the literature, the HfO 2 -TiO 2 pseudobinary systems have been investigated previously by others [17,[23][24][25], especially in view of their electrical properties [26][27][28]. As was shown by Li et al [26], mixed oxides of HfO 2 -TiO 2 had, for example, higher permittivity compared to undoped HfO 2 .…”
Section: Introductionmentioning
confidence: 82%
“…We previously reported that orthorhombic (o) HfTiO 4 in sputter deposited films on fused SiO 2 substrates demixes upon annealing to form monoclinic (m) HfO 2 and rutile (r) TiO 2 . 6,7 When demixing occurs at high temperature (1273 K), crystalline hafnon (HfSiO 4 ) with a zircon archetype lattice is formed, 8 indicating a reaction between the film and the substrate. This last result is surprising because HfSiO 4 does not form in a HfO 2 -on-SiO 2 film subjected to a similar annealing regimen.…”
mentioning
confidence: 99%
“…2(a)) shows characteristic round features associated with demixing. [6][7][8] The Raman shifts acquired from a feature and the surrounding matrix are shown in Fig. 2(b).…”
mentioning
confidence: 99%